Epitaxial synthesis of graphene on 4H-SiC by microwave plasma chemical vapor deposition - Xuemin Zhang; Changling Yan; Chunhong Zeng; Tianyu Sun; Zheng Xing; Wenhua Shi; Yiqun Wang; Chao Pang; Baoshun Zhang (Materials Research Express, 2020)
Epitaxial graphene (EG) on semi-insulating SiC prepared by a thermal decomposition method is the most promising strategy for graphene application in large-scale integrated circuits due to compatibility with current semiconductor processes. In this study, high-quality few-layer graphene (FLG) was epitaxially grown on the semi-insulating on-axis 4H-SiC by microwave plasma chemical vapor deposition (MPCVD). Both sides of the SiC substrate were etched with H _2 plasma at ∼1000 °C to promote the nucleation and the growth of graphite before epitaxial growth. The surface morphology and properties of EG on SiC (0001) were measured by energy-dispersive x-ray (EDX), x-ray photoelectron spectrogram (XPS), and atomic force microscope (AFM). The qualities of EG grown on the two surfaces of SiC at various temperatures were checked by Raman spectroscopy. Furthermore, the EG growth was controlled by the effect of Ar plasma in the MPCVD and the few-layer (1–3 layers) high-quality EG films were formed on SiC (000 $\overline{1}$ ). The room temperature Hall mobility of EGs up to 2790 cm ^2 V ^−1 s ^−1 on SiC(000 $\overline{1}$ ) was realized.